Controlled desorption of mercury in wet FGD waste water treatment. (15th January 2016) - Heidel, Barna; Rogge, Tobias; Scheffknecht, Günter
Highlights: Mercury behavior in wet FGD waste water treatment was investigated. We observed desorption of Hg 0 to the gas phase in wet FGD waste water treatment. Reaction mechanisms of Hg(II) reduction and desorption are proposed. A novel aerated waste water alkalization process is introduced. The process creates a safe, sustainable and specific sink for Hg. Abstract: This paper investigates reactions of mercury (Hg) compounds in effluents of the wet flue gas desulfurization (FGD) process during waste water treatment. Hence, a concept for the controlled desorption and immobilization of Hg is introduced. The aim is to create a highly concentrated sink for Hg for further processing. Experiments are carried out with a continuously operated lab-scale wet FGD system and a batch-wise operated alkalization reactor for the treatment of synthetic and real waste water samples. By aeration of the liquid phase, the controlled desorption of Hg during the alkalization step of the waste water treatment process is enabled. The Hg-rich exhaust air is directed to an activated carbon fixed bed adsorber. It is demonstrated, that Hg is emitted in its elemental form (Hg 0 ). Thus, a chemical reduction of dissolved Hg 2+ compounds takes place prior to Hg 0 desorption to the gas phase. Mechanisms for the reactions are proposed, identifying SO3 2− and OH − as electron donors. Linear dependency of Hg 0 formation on SO3 2− and OH − concentration indicate first order dependencies of reaction kinetics. Decreasing concentration of Hg 0 in the exhaust air for increasing Cl − concentration is observed. The results show exponential dependence of Hg 0 desorption on temperature and stirring speed. The mass flow of desorbed Hg 0 remains constant for variation in aeration flow rate. Thus, the application of low air flux is beneficial in terms of energy demand and for the purpose of creating a highly concentrated sink for Hg in the process. The concentration decrease of Hg 2+ in the waste water is proportional to the savings in terms of precipitating agent consumption of further processing steps. Finally, the concept developed prevents unnoticed Hg desorption during waste water treatment and increases sustainability and plant safety.